Efektivitas Pembelajaran Daring Berbasis Digital Classroom Bagi Siswa Sekolah Dasar (SD) Islam Al-Azhar 54 Pekanbaru - Muhammad Syahrul; Febri Yuliani (PT. ALHAFI BERKAH INDONESIA, 2023)
Al-Azhar 54 Islamic Elementary School Pekanbaru has used a new breakthrough, namely online learning based on Digital Classroom or also called learning with the E-Learning method to make it easier for students in their learning. Digital Classroom-based learning is learning that uses a device called a Tablet PC and uses special digital learning applications. The purpose of this study was to describe and analyze the effectiveness of Digital Classroom-based online learning for Islamic Al-Azhar 54 Elementary School Students in Pekanbaru and identify and analyze the Inhibiting Factors of the effectiveness of digital classroom-based online learning for Islamic Al-Azhar Elementary School Students Azhar 54 Pekanbaru. This study uses the theory of work effectiveness in the opinion of Richard M. Steers who uses 4 indicators, namely Organizational Characteristics, Environmental Characteristics, Employee Characteristics, and Management Policy and Practice. The method used in this research is a descriptive qualitative research method. With data collection techniques, namely interviews, observation, and documentation. The Effectiveness of Digital Classroom-Based Online Learning for Students of the Al-Azhar 54 Islamic Elementary School Pekanbaru has not run effectively and optimally. This is due to several factors that make the process of Effectiveness of Digital Classroom-Based Online Learning not yet effective and maximal because Teachers are not ready to carry out digital-based learning, there are still many students who do not understand or are used to digital learning and also several other factors that make learning digitally this is not optimal. So that further the effectiveness of Digital Classroom-Based Online Learning can run effectively and maximally, various aspects of the deficiencies mentioned above must be improved even better to achieve an effective and maximum learning.